Electrocatalytic hydrogen production from neutral water using an aqueous Ni(ii) pincer complex. Issue 24 (16th November 2022) - Norouziyanlakvan, Somayeh; Ferguson, Jonathan; Richeson, Darrin
Abstract : Water provides a sustainable source and solvent for electrocatalytic H2 production from a Ni(ii ) complex. Abstract : Water is the exemplary source for sustainable H2 production and provides an ideal solvent for this electrocatalytic reaction. In neutral pH, aqueous saline solution, the Ni II diminopyridiine precatalyst, [Ni(κ 3 -2, 6-PhNCMe2 (NC5 H3 ))Br2 ] 1, electrocatalytically produced H2 with an onset voltage of −1.0 V (387 mV overpotential) versus Ag/AgCl. In anhydrous acetonitrile solution, trifluoroacetic acid supplied protons for H2 production with an overpotential of 555 mV. Computational analysis (DFT) provided insight into the identities of the catalysts and supported the non-innocent role of the ligand in the reduction chemistry. Mechanistic propositions for these observations, also supported computationally, suggested proton transfer to the d z 2 -based orbital of the reduced Ni(i ) complex to generate a square planar Ni(ii ). A second proton transfer led to formation of a Ni(ii ) dihydrogen complex.